The perceptions of faculty engaged in a curricular change to project based learning in an engineering school at Brazil - Neto, Octavio Mattasoglio (2016)
The curricular change of an engineering school had as guideline the partial replacement of traditional school activities by Projects and Workshops, which put students as the main protagonists in the learning process, working actively. In this context, faculty were encouraged to propose activities that fulfil this request. Teachers from various specialties and even those who work in more advanced disciplines have submitted their proposals, which were offered to freshman students of an engineering course. The opening of the new curriculum began in 2015 when those activities were introduced in the course. The aim of this study is to know, analyze and evaluate the perception from teachers engaged in create these Projects and Workshops to this new curriculum. The survey was conducted from two focus groups, one with teachers’ proponents of Projects and other with teachers’ proponents of Workshops. The results show that the teachers attribute different meanings to the goals, strategies, evaluation and their own role in the process, though all the activities aim to ensure a common basis on engineering knowledge, which reflects the inductive character chosen in the curricular change.